Managerial Implications for Successful Teleworking Initiatives - Harvie, Arran David (2005)
Teleworking is becoming a normative working process for more employees in the construction industry. Companies are embracing technological developments to provide clients with increased perceptions of levels of service, in depth of information and also in the vehicles to communicate their knowledge. Flexible working is growing in significance for human resource managers, selecting, training and supporting a new generation of knowledge workers, often managed by an old generation of managers. In this paper we discus the managerial implications for supporting teleworking initiatives, and the increasingly strategic implications of human resource deployment away from the traditional office environment. A review of recent teleworking initiatives at an architectural practice is discussed to suggest a growing need for changing attitudes to knowledge worker management, to aid the retention of the resource value of employees following remote working experience.